Continuity of Primary Care: To Whom Does It Matter and When? - Nutting, Paul A. (Copyright 2003 Annals of Family Medicine, Inc., 2003)
BACKGROUND Inconsistent findings on the value of continuity of care can stem from variability in its importance to different subsets of patients. We therefore examined the association among patient and visit characteristics and extent to which the patient valued continuity of care (PVC). We hypothesized that continuity would be more important to patients who are older, sicker, and female, who have established a relationship with their physician, and whose visit addresses more complex problems. METHODS A study of 4,454 consecutive outpatient visits to 138 community-based family physicians used a 3-item measure (α = 0.67) of PVC. The patient’s report of (1) the adequacy of primary care for the visit and (2) satisfaction with the physician on that visit was assessed with multiple measures. Analyses examined the associations among PVC and patient-reported satisfaction with the physician and adequacy of the visit. RESULTS Extremes of age, female sex, less education, Medicare and Medicaid insurance, number of chronic conditions and medications, number of visits to the practice, and worse self-reported health status were associated with higher value placed on continuity (P <.001 for all except sex, where P = .015). Patients who value continuity and did not see a regular physician rated adequacy of the visit lower (for 7 attributes of the visit) than those seeing their own physician. Satisfaction with the physician for the visit was greatest among patients who value continuity and saw their regular physician. CONCLUSIONS Continuity of physician care is associated with more positive assessments of the visit and appears to be particularly important for more vulnerable patients. Health care systems and primary care practices should devote additional effort to maintaining a continuity relationship with these vulnerable patients.